Aluminum and ABC transporter activity - Özen, Gözde; Kraus, Lisa; Schentarra, Eva-Maria; Bolten, Jan Stephan; Huwyler, Joerg; Fricker, Gert (Environmental toxicology and pharmacology, 2024)
Aluminum is the third most common element on Earth´s crust and despite its wide use in our workaday life it has been associated with several health risks after overexposure. In the present study the impact of aluminum salts upon ABC transporter activity was studied in the P-GP-expressing human blood-brain barrier cell line hCMEC/D3, in MDCKII cells overexpressing BCRP and MRP2, respectively, and in freshly isolated, functionally intact kidney tubules from Atlantic killifish (Fundulus heteroclitus), which express the analog ABC transporters, P-gp, Bcrp and Mrp2. In contrast to previous findings with heavy metals salts (cadmium(II) chloride or mercury(II) chloride), which have a strong inhibitory effect on ABC transporter activity, or zinc(II) chloride and sodium arsenite, which have a stimulatory effect upon ABC transport function, the results indicate no modulatory effect of aluminum salts on the efflux activity of the human ABC transporters P-GP, BCRP and MRP2 nor on the analog transporters P-gp, Bcrp and Mrp2.
Gesehen am 11.09.2024